Peran Influencer marketing dan Parasocial relationship dalam Purchase decision Gen Z - Ahmad Zulfadar; Muhammad Hamdi; Maulana Ahnaf Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of influencer marketing on the purchase decisions of Indonesian Generation Z and to examine the mediating role of parasocial relationships in this relationship. The background of this study is based on Gen Z's increasing dependence on social media as a source of product information and the high influence of credibility and emotional attachment to influencers. The study used a quantitative approach through an online survey of 234 respondents who actively use social media. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that influencer marketing has a significant positive effect on parasocial relationships and purchase decisions. In addition, parasocial relationships were found to strongly mediate the relationship between the two, indicating that emotional closeness is a major factor driving Gen Z's purchasing decisions. These findings confirm the importance of authenticity and social connectedness in influencer marketing strategies. This study provides theoretical and practical contributions to the development of parasocial relationship based digital marketing strategies.